Synthesis of CuO Nanoparticles from Copper(II) Schiff Base Complex: Evaluation via Thermal Decomposition - Al-Khazraji, Ali Mudher Abdulkareem; Waheed, Enass Jasim; Ahmed, Awf Abdul Rahman (Indonesian Journal of Chemistry, 2025)
Copper oxide (CuO) nanoparticles were synthesized through the thermal decomposition of a copper(II) Schiff-base complex. The complex was formed by reacting cupric acetate with a Schiff base in a 2:1 metal-to-ligand ratio. The Schiff base itself was synthesized via the condensation of benzidine and 2-hydroxybenzaldehyde in the presence of glacial acetic acid. This newly synthesized symmetric Schiff base served as the ligand for the Cu(II) metal ion complex. The ligand and its complex were characterized using several spectroscopic methods, including FTIR, UV-vis, 1H-NMR, 13C-NMR, CHNS, and AAS, along with TGA, molar conductivity and magnetic susceptibility measurements. The CuO nanoparticles were produced by thermally decomposing the complex at 800 °C. These nanoparticles and other metal oxides are highly valued in various industries for their optical, magnetic, and electrical properties. The experiment highlighted the synthesis of CuO nanoparticles through the thermal breakdown of copper(II) ions, starting with copper acetate, which reacted with the ligand to form the complex. The characterization results of CuO nanoparticles reveal a highly pure crystalline structure with an average size of 70–90 nm.